Acoustic Ecology: A Case Study of the Soundscape of Loreta Square in Prague - Griger, Ján (Lidé města, 2007)
This diploma thesis is based on key theoretical concepts of acoustic ecology and soundscape and is divided into two main parts. In first part of the thesis I discussed three main approaches to research of subjective perception and interpretation of everyday sound environment: the ecological approach of WSP, Truax’s acoustic communication approach, and the structural approach of Augoyard and Amphoux of the CRESSON research institute. Concerning each approach I discussed the basic terms and method (or methods) used for soundscape research. In the second part of the thesis I described each phase and made an analysis of the results of the field research of the soundscape of Loreta Square in Prague. The research was done with questionnaires, and two main approaches were used: one place-oriented approach (subjective perception and interpretation of the everyday soundscape of all of Loreta Square) and one sound-oriented approach (subjective perception and interpretation of the sound of the Loreta Carillon). In the following text I will focus on the historical background of acoustic ecology and on the results of field research.